Radix Entomolaris in Mandibular First Molar: An Endodontic Challenge (Bangladesh Journal of Dental Research & Education, 2015)
Success of endodontic therapy depends on the proper identification of all the canals, thorough chemo-mechanical preparation followed by three dimensional obturation with fluid tight seal. Failure of any of these steps may occur due to unusual tooth morphology. Proper knowledge of root canal anatomy is a basic prerequisite for the endodontic treatment successful. Mandibular molars may have an additional root located lingually (radix entomolaris) or buccally (radix paramolaris). Awareness and understanding of the presence of unusual external and internal root canal morphology contributes to the successful outcome of the root canal treatment.Bangladesh Journal of Dental Research and Education Vol.5(2) 2015: 66-69